2011
DOI: 10.1037/a0022469
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from child sexual abuse to adult depression: The role of parental socialization of emotions and alexithymia.

Abstract: Depression is common among adult survivors of child sexual abuse (CSA), but the intervening processes responsible for this outcome have not yet been fully delineated. The present study investigated the mediating role of perceived parental emotion socialization and alexithymia (difficulties identifying and describing feelings) in explaining the link between CSA and adult depressive symptoms in female veterans. Method: Cross-sectional data were collected from 110 female veterans who completed self-report questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 62 publications
1
26
2
1
Order By: Relevance
“…Our findings show that trauma does in fact impede on the capacity to identify and express feelings, which in turn increases the level of psychological distress of teenagers. Our results support previous findings among adults showing that CSA victims are characterized by higher levels of alexithymia (Thomas et al, 2011). As posited by Lecours et al (2016), negative affects generated by the trauma could explain this association.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings show that trauma does in fact impede on the capacity to identify and express feelings, which in turn increases the level of psychological distress of teenagers. Our results support previous findings among adults showing that CSA victims are characterized by higher levels of alexithymia (Thomas et al, 2011). As posited by Lecours et al (2016), negative affects generated by the trauma could explain this association.…”
Section: Discussionsupporting
confidence: 92%
“…While some studies found that adult survivors of CSA are likely to display higher levels of alexithymia (Scher and Twaite, 1999;Thomas et al, 2011), more recent studies failed to find a link between CSA and alexithymia (Şenkal and Işikli, 2015;Brown et al, 2016). These discrepant results may be linked to methodological issues and limitations such as a small number of participants disclosing CSA in the samples considered as well as reliance on cross-sectional designs (Taylor and Bagby, 2013).…”
Section: Alexithymia and Csamentioning
confidence: 99%
“…Although moderately correlated (r values = 0.18-0.44; see Table 2), the three types of avoidance seemed to be separate firstorder latent constructs. The existing literature provides supporting evidence that each type of avoidance is uniquely related to trauma experience and posttraumatic symptomology (Brewin and Patel, 2010;Frewen et al, 2008;Kumpula et al, 2011;Ozer et al, 2003;Thomas et al, 2011). Although previous studies have investigated each type of avoidance separately, the current study expands current literature by including all types of avoidance in one study to compare their unique influences.…”
Section: Discussionmentioning
confidence: 75%
“…Alexithymia has also been linked to a variety of negative mental health and behavioral outcomes, including depression, anxiety, anger, feelings of shame, and violence perpetration (Freyberger, 1977;Thomas et al, 2011;Zimmermann et al, 2005). Research indicates a high prevalence of alexithymia in individuals with PTSD symptomology (Frewen et al, 2008(Frewen et al, , 2012.…”
Section: Alexithymiamentioning
confidence: 99%
“…La ideación o conducta suicida también parecen ser más comunes en las víctimas de abuso sexual (Beitchman, et al, 1991;Putnam, 2003). Además, se ha descrito la relación con otros cuadros psicopatológicos como depresión (Thomas, DiLillo, Walsh & Polusny, 2011), trastorno por estrés pos traumático (Guerrero, Torres & Conde, 2012), trastorno límite de personalidad (Machizawa-Summers, 2007), trastorno antisocial de la personalidad (Semiz, Cengiz, Servet & Mesut, 2007) y consumo de drogas y alcohol (Bebbington et al, 2011).…”
Section: Efectos Psicológicos Del Abuso Sexual Infantilunclassified